Trehalose attenuates development of nonalcoholic steatohepatitis associated with type 2 diabetes in TSOD mouse. (May 2019) - Murotomi, Kazutoshi; Arai, Shigeyuki; Suyama, Aki; Harashima, Akira; Nakajima, Yoshihiro
Graphical abstract: Highlights: Trehalose intake markedly attenuates NASH manifestation in TSOD mouse. Impaired glucose tolerance in TSOD mouse is also prevented by trehalose intake. Trehalose has the potential to prevent NASH associated with type 2 diabetes. TSOD mouse is useful for evaluation of drug candidates against metabolic syndrome. Abstract: Trehalose, a non-reducing disaccharide, induces autophagy. Trehalose mitigates insulin resistance and adipocyte hypertrophy in obese mice; however, its effect on the development of nonalcoholic steatohepatitis (NASH) associated with type 2 diabetes remains unknown. In this study, we investigated the effect of trehalose on the development of NASH in the Tsumura Suzuki Obese Diabetes (TSOD) mouse, a metabolic syndrome model characterized by obesity, type 2 diabetes, and NASH. We found that trehalose intake markedly inhibited histopathological features of NASH, particularly hepatic steatosis and liver cell injury, in TSOD mice. Trehalose intake attenuated increase in mesenteric adipose tissue weight, impaired glucose tolerance, and iron deposition in the duodenum, suggesting that trehalose prevents insulin resistance and iron absorption in TSOD mice. These findings indicate that trehalose attenuates the development of NASH associated with type 2 diabetes, and this attenuation may be mediated by prevention of lipid accumulation and iron absorption.